The standard of living in eighteenth-century Spain - Héctor GARCÍA-MONTERO (Cuadernos Dieciochistas)
This work provides a literature review of the research which dealt with the analysis of living standards in 18th-century Spain. At the same time, possible fields of research are suggested for the future. The text focuses on three types of indicators: material well-being and economic inequality (GDP per capita, real wages and Gini index), bio-nutritional (average height) and demographic (mortality and life expectancy) indicators. The available evidence points to a slightly positive balance in terms of material well-being, nuanced by an increase in economic inequality in the second half of the century, a drop in net nutritional status among those born in the final decades of the century, and a drop in mortality rates in the second half of the century, which was determined by a decline in ordinary and adult mortality.